Aircrafts Dedicated Guidance System based on improved mathematical model with Modern Visual Presentation - Łąkowski, Paweł; Szablata, Piotr; Pochmara, Janusz (Biuletyn Wojskowej Akademii Technicznej, 2023)
This paper aims to introduce an alternative method of navigating aerial transportation. Its goal is to aid pilot while conducting two most dangerous operations: taking off and landing the plane. Proposed system novelty lies in its separation from all the other systems available on deck. Any fault of hardware or software on the plane will not influence the proposed system. It will offer second set of data for the pilot, precise information about what is visible from the position of the sensor — at the bottom of fuselage. This can greatly increase safety while conducting manoeuvres in bad weather conditions. We also believe that we reached simplicity and cost of implementation of the proposed system at a level good enough to make this idea very popular among industry specialists. From the perspective of mathematical specialist, it offers interesting point of view on methods how algorithm and equation were created.Keywords: aircraft system, algebraical analyse of approach, approach landing system, intelligent aircraft system, visual aircraft system